National Incident-Based Reporting System, 2019: Extract Files ([Verlag nicht ermittelbar], 2022)
The National Incident-Based Reporting System (NIBRS) is a part of the Uniform Crime Reporting Program (UCR), administered by the Federal Bureau of Investigation (FBI). NIBRS is an annual data collection that compiles information on criminal incidents and arrests reported by participating law enforcement agencies. NIBRS data as formatted by the FBI are stored as a series of single files organized by various segment levels (record types). There are six main segment levels: administrative, offense, property, victim, offender, and arrestee. Each segment level has a different length and layout. Significant computing resources are necessary to work with the data in its single-file format. In addition, the user must be knowledgeable about working with data in complex file types. The extract files version of the NIBRS files was created to simplify working with NIBRS data. Data management issues with NIBRS are significant, especially when two or more segment levels are being merged. For these reasons and the desire to facilitate the use of NIBRS data, ICPSR created the extract files. The data are not a nationally representative sample of crime in the United States.